2018
DOI: 10.5539/jas.v10n7p258
|View full text |Cite
|
Sign up to set email alerts
|

Management of Meloidogyne javanica in Okra Using Compost of Pequi Fruit Waste

Abstract: Pequi waste added to soil can lead to promising results in the management of plant nematodes. This study evaluated the effect of organic compost of pequi fruit waste in the control of Meloidogyne javanica in okra plants. The compost was comprised of cattle manure, sugarcane straw, and pequi rind waste in the ratio 1:1:1. Treatments were five doses of organic compost (0, 5, 10, 20, and 30 g dm -3 ) and two additional controls: manure (20 g dm -3) and mineral fertilizer (100 mg dm -3 of N), arranged in rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Some studies have shown that tannins reduce the hatch rate, inactivate Meloidogyne spp. and consequently reduce the number of galls [ [44] , [45] , [46] , [47] ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that tannins reduce the hatch rate, inactivate Meloidogyne spp. and consequently reduce the number of galls [ [44] , [45] , [46] , [47] ].…”
Section: Resultsmentioning
confidence: 99%
“…Seedlings of P. guineense (resistant to the nematode) [ 42 ], of P. guajava cv. Paluma (susceptible to the nematode) [ 44 ] and of P. cattleianum (immune to the nematode) [ 46 ] were obtained by germinating seeds in a greenhouse at Embrapa Semiarid, Petrolina, PE (Latitude: 9°09′S, Longitude 40°22′W, at an altitude of 365.5 m) with proper cultural practices.…”
Section: Methodsmentioning
confidence: 99%